The Effect of Ease of Use and E-Trust on User Purchase Decisions - Delfian Delfian; Abdul Yusuf (Almana : Jurnal Manajemen dan Bisnis, 2022)
Fintech (Financial Technology) in Indonesia continues to grow and experience a rapid increase, one of the most widely used Fintech products is a digital wallet (e-wallet). Ease of Use and E-Trust play an important role in making Purchase Decisions, Ease of Use can be seen in terms of the ease of using a system, and E-Trust in terms of very high trust can create a good relationship between the Dana application and its users. This study aims to determine how much influence Ease of Use and E-Trust have on Purchase Decisions on Dana digital wallet users. The research method used is a quantitative method with a descriptive and verification approach, while the data used in this study are primary data obtained from the questionnaire results. Data testing was done by descriptive analysis, verification analysis, and hypothesis testing using SPSS 24. The results showed that Ease of Use Dana, E-Trust Dana, and Purchase Decisions Dana was in a good category. There is a correlation between Ease of Use and E-Trust, there is a partial effect between Ease of Use and E-Trust on Purchase Decisions, and there is a simultaneous effect between Ease of Use and E-Trust on Purchase Decisions.